ASSESSING THE BIOMASS PRODUCTION AND NUTRITIVE VALUE OF KENAF (HIBISCUS CANNABINUS) AT VARIOUS STAGES OF GROWTH - Ziblim, A. I.; Agyapong, R. A.; Aikins, T. K. (UDS International Journal of Development, 2016)
This study was carried out to evaluate the yield and chemical composition of Kenaf at different stages of growth. Nine (9) beds were constructed, each measuring 2 ×2m with a distance of 1m between them. Kenaf seeds were planted on the beds at 0.4 m between and within rows with a planting depth of 2.5 cm. Germination was observed three (3) days after planting and the following data were collected weekly for 9 weeks; plant heights, number of leaves and stem girth (diameter). Leaves, stems and roots were separated and dried in an oven at 650 C for 48 hours until a constant weight was obtained for biomass determination. Both proximate (crude fibre, crude protein and carbohydrates) and elemental (N, P, K, Ca, Mg) analyses were carried out on Hibiscus cannabinus. Crude protein content decreased significantly from 5 week after planting (WAP) to 9 WAP (from 24.1 % to 17.6 %). Plant height was noted to have a perfect positive linear relationship (r= 0.991) with the number of leaves of the plant. The results also revealed that dry matter yield of Hibiscus cannabinus was 288.1 kg/ha at the end of the study. Conclusively, harvesting Hibiscus cannabinus at 5 WAP is the most appropriate stage for higher proportions of nutrients concentration. Specifically, for high crude protein concentration (24.1 %), Hibiscus cannabinus should be harvested at 5 WAP as fodder for animals. Keywords: Kenaf, Forage, Elements, Proximate, Biomass